Pengaruh Personalized Ubiquitous Learning Dan Self Regulated Learning Terhadap Hasil Belajar Matematika SMP - Tonge, Marselinus; Kuswandi, Dedi; Ulfa, Saida (Universitas Negeri Malang, 2023)
Personalized u-Learning environments can enhance context-aware learning experiences and provide personalized learning opportunities. Personalized u-Learning supports interaction between authentic and digital learning resources. This study tested the learners' u-learning and Self Regulated Learning (SRL) strategies on mathematics learning outcomes in students of Frater Maumere Catholic Junior High School. The study used quasi-experimental design. The research design used is a non-equivalent control group design. The instruments to measure learning outcomes are objective tests and SRL questionnaires (OSLQ) adapted from Barnard to determine the SRL of the subjects studied. The data is then analyzed through the two-way ANOVA technique. The results of the study found several important findings: First, there was a significant difference in the mathematics learning outcomes of students who used the u-learning learning strategy with the e-Learning strategy. Second, there were significant differences in the learning outcomes of groups that had high SRL levels with low SRL levels. Third, there is an interaction of U-learning and e-learning strategies with high SRL and low SRL levels that affect learner learning outcomes.AbstrakLingkungan pembelajaran u-Learning yang dipersonalisasi dapat meningkatkan pengalaman belajar sadar konteks dan memberikan kesempatan belajar personal. Personalized u-Learning mendukung interaksi antara sumber belajar otentik dan digital. Penelitian ini menguji strategi u-learning dan Self Regulated Learning (SRL) pebelajar terhadap hasil belajar matematika pada siswa SMP Katolik Frater Maumere. Penelitian menggunakan kuasi eksperimen (quasi-eksperimental design). Rancangan penelitian yang dipakai adalah non-equivalent control group design. Instrumen untuk mengukur hasil belajar adalah tes objektif dan angket SRL (OSLQ) diadaptasi dari Barnard untuk mengetahui SRL subyek yang diteliti. Data tersebut kemudian dianalisis melalui teknik two-way ANOVA. Hasil penelitian menemukan beberapa temuan penting: Pertama, Ada perbedaan yang signifikan hasil belajar matematika peserta didik yang menggunakan strategi pembelajaran u-Learning dengan strategi e-Learning. Kedua, terdapat perbedaan signifikan dalam hasil belajar kelompok yang memiliki tingkat SRL tinggi dengan tingkat SRL rendah. Ketiga, ada interaksi strategi u-Learning dan e-Learning dengan tingkat SRL tinggi dan SRL rendah yang mempengaruhi hasil belajar pebelajar.